Optimum Space Utilization Approach to Improve Persistence of WSNs (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
Wireless Sensor Networks (WSNs) are consists of huge number of sensor nodes, restricted with limited power, Â for provide services with cooperation to sense data and send to server. Various routing techniques are introduced for managing data transmission in WSNs in last decade. This work proposes novel method with compare distance of sensor nodes to base station in heterogeneous WSN. The sensor nodes near to base station are likely to send data direct to base station and nodes are long distance to base station would form cluster to send data using Stable Election Protocol (SEP) method. This work considers distance parameter to compare with base station position to decide whether need for nodes clustering or not. The proposed method further compare with existing Low Energy adaptive clustering hierarchy (LEACH) protocol and SEP protocol for WSN data transmission. The proposed method simulation results show the effectiveness with compare to existing methods.